Social Media, Civic Vitality and Nigerias 2019 General Elections - Nwoke, Chikezirim C.; Oyiga, Stanley C.; Ihuoma, Chiadikobi H. (Covenant Journal of Communication, 2021)
This paper explores civic vitality in Nigeria in the build-up to and after the country's 2019 elections. This study was motivated by widening the research trajectory, especially in citizens political expression, voter education, electioneering, and mobilization. It investigates Facebook and Twitter subscribers from the cyber-ethnographic standpoint via the qualitative and quantitative methods. The findings show that while social media platforms enhance these civic vitality areas, this performance does not translate to realtime political participation in any significant way. The assertion is therefore confirmed: online activities are no good predictors of election undertakings or outcomes.